Optimization of Water Treatment Parameters using Processed Moringa oleifera As a Natural Coagulant for Low Turbidity Water - Ali, Eman N.; Suleyman, A. Muyibi; Md Zahangir, Alam; Hamzah, M. Salleh (2012)
Moringa oleifera is a natural coagulant which can be used for water treatment in tropical developing countries. This study presents the results of production of natural coagulant from processed Moringa oleifera with simple technique (oil extraction, salt extraction, and microfiltration with 0.2 μm). The optimization study on physical factors was carried out for coagulation-flocculation process. Low initial turbidity water samples (synthetic and river water) were used with turbidity less than 50 Nephelometric Turbidity Units (NTU). The response surface methodology (RSM) was used, and the analysis of variance (ANOVA) was performed to validate the developed regression model. The residual turbidity obtained was 4.514 NTU for synthetic water and 1.598 NTU for river water by applying the optimum conditions of 40 rpm (low speed), mixing time of 41 minutes, and Moringa oleifera dosage of 0.75 mg/L.